2007
DOI: 10.1016/j.bbrc.2007.05.119
|View full text |Cite
|
Sign up to set email alerts
|

LIGHT, a member of the TNF superfamily, activates Stat3 mediated by NIK pathway

Abstract: Stat3, a member of the signal transducers and activators of transcription (STAT) family, is a key signal transduction protein activated by numerous cytokines, growth factors, and oncoproteins that controls cell proliferation, differentiation, development, survival, and inflammation. Constitutive activation of Stat3 has been found frequently in a wide variety of human tumors and induces cellular transformation and tumor formation. In this study, we demonstrated that LIGHT, a member of tumor necrosis factor supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
0
28
1
Order By: Relevance
“…A previous study showed that NIK could function as a serine kinase of STAT3; however, the high basal levels of serinephosphorylated STAT3 in NIK-defective cells indicate that other kinases may also phosphorylate STAT3 (39). To confirm the requirement for NIK in LMP1-induced EGFR expression, CTAR1-expressing C33A cells were transiently transfected with a dominant negative NIK construct (DNNIK), DNNIK with an aly mutation (G860R; NIK-aly), or kinase-dead NIK [NIK(K-A)] for 48 h, and the expression levels of EGFR and serine-phosphorylated STAT3 were analyzed by immunoblotting (Fig.…”
Section: Lmp1 Effects On Egfr Expression In Mouse Embryonic Fibroblasmentioning
confidence: 95%
See 1 more Smart Citation
“…A previous study showed that NIK could function as a serine kinase of STAT3; however, the high basal levels of serinephosphorylated STAT3 in NIK-defective cells indicate that other kinases may also phosphorylate STAT3 (39). To confirm the requirement for NIK in LMP1-induced EGFR expression, CTAR1-expressing C33A cells were transiently transfected with a dominant negative NIK construct (DNNIK), DNNIK with an aly mutation (G860R; NIK-aly), or kinase-dead NIK [NIK(K-A)] for 48 h, and the expression levels of EGFR and serine-phosphorylated STAT3 were analyzed by immunoblotting (Fig.…”
Section: Lmp1 Effects On Egfr Expression In Mouse Embryonic Fibroblasmentioning
confidence: 95%
“…IKK␣ has also been implicated in the phosphorylation of several nuclear substrates, including SMRT, histone H3, and CBP (16,17,58). NIK was recently suggested to function as a serine kinase of STAT3 (39). The aberrant regulation of NF-B activation pathways has been implicated in development of many human cancers (34,44).…”
mentioning
confidence: 99%
“…More than 40 different polypeptide ligands cause STAT phosphorylation. STAT3 is activated in response to many cytokines such as IL-6 [48], leukemia inhibitory factor (LIF) [49], cardiotrophin-1 [50], ciliary neurotrophic factor (CNTF) [51], IL-5 [52], IL-9 [53], IL-10 [54], IL-11 [55], IL-12 [56], IL-21 [57], IL-22 [58], IL-27 [59], IFN-γ [60], TNF-α [61], LIGHT, a member of the TNF superfamily [62], monocyte chemotactic protein-1 (MCP-1) [63], macrophage inflammatory protein-1α (MIP-1α) [64], CCL-5/RANTES [64], stem cell factor (SCF) [65], oncostatin M (OSM) [66]), growth factors (e.g., EGF [67], TGFα [61], PDGF [68], IGF-1 [69], G-CSF [70], M-CSF [71] and GM-CSF [52]) and oncogenic proteins through phosphorylation of tyrosine 705. In addition, numerous carcinogens (e.g.…”
Section: Stat3 Activation By Diverse Agentsmentioning
confidence: 99%
“…32 Moreover, overexpressed NIK induces the phosphorylation of STAT3 in a prostate cancer cell line. 33 Notably, the catalytic activity of NIK is rapidly stimulated upon ligation of TCR and the costimulatory molecule CD28, 34 suggesting a role for NIK in regulating the signaling events involved in T-cell activation or differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…32 Moreover, overexpressed NIK induces the phosphorylation of STAT3 in a prostate cancer cell line. 33 Notably, the catalytic activity of NIK is rapidly stimulated upon ligation of TCR and the costimulatory molecule CD28, 34 suggesting a role for NIK in regulating the signaling events involved in T-cell activation or differentiation.In the present study, we investigated the function of NIK in T-cell differentiation using NIK knockout mice. We show that NIK has a critical role in Th17 cell differentiation and EAE induction, although this MAP3K is dispensable for the differentiation of Th1, Th2, and iTreg cells.…”
mentioning
confidence: 99%